RECONHECIMENTO FACIAL PARA CONTROLE DE FREQUÊNCIA DE ALUNOS (REMUNOM, 2024)
Facial recognition is a technology that has been applied in several areas, including education. Built from a literature review, this article addresses the use of facial recognition to control student attendance, which has varied benefits, including improvements in school security and efficiency in attendance control. Despite advances, there are challenges to be overcome, including the accuracy of facial recognition and the investment required to implement the technology on a massive scale. The use of facial recognition in schools raises important ethical questions regarding privacy and consent. It is important for schools to establish clear policies and be transparent about the use and storage of data.